Direct alloying of immiscible molybdenum-silver system and its thermodynamic mechanism. (28th February 2021) - Du, Jinlong; Li, Cai; Wang, Zumin; Huang, Yuan
Abstract: Direct alloying is difficult to be realized in an immiscible Mo-Ag system with a positive formation heat due to the absence of thermodynamic driving force at equilibrium. In this work, a direct alloying method is developed to realize the direct alloying between Mo and Ag and construct Mo-Ag interface. The direct alloying method was mainly carried out through a direct diffusion bonding for Mo and Ag rods at a temperature close to the melting point of Ag (TmAg ). Then the microstructure and phase constitution of the as-constructed Mo-Ag interface are characterized. The results show that Mo-Ag metallurgical bonding interface has been constructed successfully, indicating that a direct alloying in the immiscible Mo-Ag system has been realized. Additionally, mechanical tests are carried out for the Mo-Ag joints prepared through the direct alloying method. The test results show that the average maximum tensile strength of the joints is about 107 MPa. The effect of alloying parameters on the tensile strength is also discussed, which shows that there is an effective temperature range for the direct alloying between Mo and Ag. Lastly, an improved thermodynamic model that considers the formation of Mo-Ag crystalline and amorphous phase is presented to reveal the thermodynamic mechanism of the direct alloying. Combining the calculation and differential scanning calorimetry (DSC) tests results, the Gibbs energy diagram for the direct alloying is obtained. It is confirmed that the co-release of storage energy and surface energy can serve as the thermodynamic driving force to overcome the effect of positive formation heat and lead to direct alloying for Mo-Ag systems.